Simultaneous subcortical and cortical electrophysiological recordings of spectro-temporal processing in humans - Calcus, Axelle; Undurraga, Jaime A.; Vickers, Deborah (Frontiers in Neurology, 2022)
Objective assessment of auditory discrimination has often been measured using the Auditory Change Complex (ACC), which is a cortically generated potential elicited by a change occurring within an ongoing, long-duration auditory stimulus. In cochlear implant users, the electrically-evoked ACC has been used to measure electrode discrimination by changing the stimulating electrode during stimulus presentation. In addition to this cortical component, subcortical measures provide further information about early auditory processing in both normal hearing listeners and cochlear implant users. In particular, the frequency-following response (FFR) is thought to reflect the auditory encoding at the level of the brainstem. Interestingly, recent research suggests that it is possible to simultaneously measure both subcortical and cortical physiological activity. The aim of this research was twofold: first, to understand the scope for simultaneously recording both the FFR (subcortical) and ACC (cortical) responses in normal hearing adults. Second, to determine the best recording parameters for optimizing the simultaneous capture of both responses with clinical applications in mind. Electrophysiological responses were recorded in 10 normally-hearing adults while they listened to 16-second-long pure tone sequences. The carrier frequency of these sequences was either steady or alternating periodically throughout the sequence, generating an ACC response to each alternation—the alternating ACC paradigm. In the “alternating” sequences, both the alternating rate and the carrier frequency varied parametrically. We investigated three alternating rates (1, 2.5, and 6.5 Hz) and seven frequency pairs covering the low-, mid-, and high-frequency range, including narrow and wide frequency separations. Our results indicate that both the slowest (1 Hz) and medium (2.5 Hz) alternation rates led to significant FFR and ACC responses in most frequency ranges tested. Low carrier frequencies led to larger FFR amplitudes, larger P1 amplitudes, and N1-P2 amplitude difference at slow alternation rates. No significant relationship was found between subcortical and cortical response amplitudes, in line with different generators and processing levels across the auditory pathway. Overall, the alternating ACC paradigm can be used to measure sub-cortical and cortical responses as indicators of auditory early neural encoding (FFR) and sound discrimination (ACC) in the pathway, and these are best obtained at slow alternation rates (1 Hz) in the low-frequency range (300–1200 Hz).